Horizontal transfer and subsequent explosive expansion of a DNA transposon in sea kraits (Laticauda). (1st September 2021) - Galbraith, James D.; Ludington, Alastair J.; Sanders, Kate L.; Suh, Alexander; Adelson, David L.
Abstract : Transposable elements (TEs) are self-replicating genetic sequences and are often described as important 'drivers of evolution'. This driving force is because TEs promote genomic novelty by enabling rearrangement, and through exaptation as coding and regulatory elements. However, most TE insertions potentially lead to neutral or harmful outcomes, therefore host genomes have evolved machinery to suppress TE expansion. Through horizontal transposon transfer (HTT) TEs can colonize new genomes, and since new hosts may not be able to regulate subsequent replication, these TEs may proliferate rapidly. Here, we describe HTT of the Harbinger-Snek DNA transposon into sea kraits ( Laticauda ), and its subsequent explosive expansion within Laticauda genomes. This HTT occurred following the divergence of Laticauda from terrestrial Australian elapids approximately 15–25 Mya. This has resulted in numerous insertions into introns and regulatory regions, with some insertions into exons which appear to have altered UTRs or added sequence to coding exons. Harbinger-Snek has rapidly expanded to make up 8–12% of Laticauda spp. genomes; this is the fastest known expansion of TEs in amniotes following HTT. Genomic changes caused by this rapid expansion may have contributed to adaptation to the amphibious-marine habitat.